Respuesta :

Answer:

-108  

Step-by-step explanation:

ok, so if x=2 and y= -4 and your equation given in the question is -3(x-y)[tex]^2[/tex]  

so we simply input our values of x and y given

-3(2-(-4))[tex]^2[/tex]

word of advice to make your calculations and answers more precise always deal with numbers in bracket

I used a bracket for 4 because its carrying a minus/ negative sign and two negative multiplied gives a positive .

so, this will give you;

-3(2+4)[tex]^2[/tex]= -3(6)[tex]^2[/tex]

the square will only affect the number in the bracket

(6)[tex]^2[/tex] = 6x6 =36

-3(36)= -3 x 36= -108